RANCANG BANGUN PROTOTIPE MEKANISME PEMBUKA PINTU PADA ROBOT ASISTEN MEDIS - Suryawan, Donny; Qadim, Muhammad Al; Adi, Agung Nugroho; Purtojo, Purtojo; Rinaldi, Rahmat Irvan; Alfian, Fariz (Jurnal Teknologi Terapan, 2025)
The total number of health workers who died from COVID-19 infection reached two thousand people. The number of victims from medical personnel certainly needs to be a concern. Reducing the contact of medical workers with infected patients is an alternative solution to reduce the number of victims. Medical assistant robots are an alternative solution for helping medical workers to provide service to the infected patient. But, the most medical assistant robot did not have a mechanism to open the door. So, the robot becomes less effective if the health workers still have to open the door for the robot. Because of that, it is very crucial to develop a mechanism to open the door on a medical assistant robot. The research is focused on developing an opening door mechanism for the medical assistant robot that was made before. The results show that the opening door mechanism can help the medical assistant robot open the door. The test results also show that none of the door opening processes failed during ten times testing.